Teacher-Student Relationship Quality and Children's Bullying Experiences With Peers: Reflecting on the Mesosystem - Bouchard, Karen L.; Smith, J. David (The Educational forum (West Lafayette, Ind.), 2017)
Drawing from social-ecological systems theory, the authors argue that -current research on childhood bullying would benefit from analyses that consider the -mesosystem-specifically, how teacher-student relationships can influence -children's bullying experiences. The authors provide two theoretical conceptions for how children's peer interactions are implicitly shaped by teacher-student relationship quality: attachment and social referral. Implications for practice, with an emphasis on developing teachers' social-emotional competencies to strengthen positive teacher-student relationships, are proposed.